The use of electrolytically detachable coils in treating high-flow arteriovenous fistulas. - Nesbit, G M; Barnwell, S L (American Journal of Neuroradiology, 1998)
BACKGROUND AND PURPOSE High-flow arteriovenous fistulas (AVFs) are commonly treated by using an endovascular approach with a variety of materials. The use of a Guglielmi electrolytically detachable coil (GDC) provides the ability to reposition or remove the coil if its position is not optimal and may minimize the risk of coil migration or distal embolization. This study reports our experience in using these coils alone or in combination with other materials in the treatment of intracranial and cervical high-flow fistulas.METHODS Twelve patients with AVFs were treated with GDCs via the transvenous or transarterial-transfistulous routes. The six dural AVFs treated transvenously were also treated transarterially, and the GDCs were combined with fibered coils in three of these patients and in two other patients with pial AVFs. All patients have been clinically followed up for 12 to 48 months (mean, 28 months).RESULTS Angiographic obliteration was obtained in all 12 patients. The fistulas have remained closed in 11 patients, as ascertained by angiographic confirmation in two patients and by clinical examination in nine patients. The one patient with recurrence experienced neurologic improvement and refused further treatment. GDCs required repositioning before detachment in seven patients, and no migration occurred after detachment.CONCLUSION GDCs are useful for the treatment of high-flow AVFs. They afford more control in the placement of coils and may provide an anchoring point for more thrombogenic materials.